Bullied, anxious and skipping school? the interplay of school bullying, school anxiety and school absenteeism considering gender and grade level - Schlesier, Juliane; Vierbuchen, Marie-Christine; Matzner, Matthias (Frontiers in Education, 2023)
The topics of bullying, school anxiety and school absenteeism are of steady interest for the scientific community in recent decades. However, it seems surprising that investigations into the combination of these constructs are rare, especially considering their interconnectedness. Due to the lack of joint investigation of these factors, it is hardly possible to compare results of these related, yet distinct factors across other studies, let alone the predictive power of specific factors. The goal of the current study is to investigate how bullying, school anxiety and school absenteeism are related, considering the variables gender and grade level. For this purpose, N = 195 secondary school children in the 7th to 9th grades in northern Germany were surveyed via self-report questionnaires and additionally collecting their school records. We present complex descriptive analyses with scales and subscales of bullying, anxiety and absenteeism. Further, a structural equation modelling (SEM) approach is utilised to discover the interconnectedness of the constructs. On the one hand, the descriptive statistics show significant gender and grade level differences regarding bullying and anxiety. On the other hand, the SEM reveals that high values on the bullying victim scale are accompanied by significantly higher school displeasure (anxiety). School displeasure – as well as high bullying offender values – are associated with significantly more days of absence from school. We discuss how school environment improvement through specific interventions such as the cognitive-behavioural approach, could aid to ameliorate this issue.